Marketing Performance: Digital Marketing and Marketing Ability Moderated by Government Policies (The Owner of Snack UMKM in Bekasi Regency) - Tanjung, Agustini; Hermiyetti; Parkhurst, Helen; Young, Felina Co (Maneggio, 2024)
MSMEs in Indonesia contribute to national economic income progressing from year to year. This research aims to analyze the small snack business category of MSMEs activities in Bekasi Regency developing the businesses and determine the impact of Digital Marketing and Marketing Capabilities on Marketing Performance moderated by Government Policy. The research model is quantitative with non-probability sampling and primary and secondary data is used. Data analysis usage is descriptive statistical analysis, and inferential analysis through SmartPLS version 3. This research approached and processed 170 small snack business actors in Bekasi Regency as prime data. The research results show that digital marketing had a significant influence on marketing performance since the result of T value>T table (2,857>1,974) P value (0.004<0.05). Marketing capabilities had a significant influence on marketing performance since the result of T value>T tabel (2,870>1,974) P value (0.004<0.05). Government policy as a moderating variable on digital marketing influenced marketing performance affected but not significant since T value<T value (1,582<1,974). Government policy as a moderating variable on marketing ability influenced marketing performance affected but not significant since T value<T value (1,280<1,974). Meanwhile, the results of the termination test (R Square) explained both digital marketing and marketing capability influenced marketing performance 62.10%